Detection of pYV+ Yersinia enterocolitica isolates by P1 slide agglutination. - Sory, M P (1990)
Rabbit polyclonal antisera were raised against the pYV-encoded outer membrane protein P1 of five Yersinia enterocolitica strains belonging to serogroups O:3, O:5,27, O:8, and O:9. Analysis of these strains with the sera showed that P1 presented at least six different antigenic factors. Two of the serum specimens were chosen to test the P1 agglutinability of 797 strains isolated from various sources. This technique appeared to be more reliable than autoagglutination and Ca2+ dependency to monitor the presence of the pYV plasmid. Hence, we propose this P1-mediated agglutination as a new and easy virulence test.